Harmonic minimization of a single-phase asymmetrical TCHB multilevel inverter based on nearest level control method - Wail Ali Ali Saleh; Nurul Ain Mohd Said; Wahidah Abd Halim (Institute of Advanced Engineering and Science, 2020)
Multilevel inverters are gaining special interest among researchers and in the industry due to their widespread applications and numerous merits. Obtaining high quality, more reliable output while using a reduced number of electronic components is the main purpose of most of the research conducted in this area of study. The purpose of this study is to apply the nearest level control (NLC) method to a 13-level transistor-clamped H-bridge (TCHB) inverter with unequal DC voltage supplies. The NLC method operates at the fundamental frequency, thus reducing switching losses, and can reduce the harmonic content significantly. The adopted multilevel inverter consists of two TCHB cells supplied with two asymmetrical DC input sources with a voltage ratio of 1:2. This structure reduces the number of electronic components, and the asymmetry in the DC input voltages results in a higher number of levels. The adopted topology and its proposed control method were simulated in Matlab/Simulink, and the simulation results were verified through experiments using an Altera field-programmable gate array (FPGA) board. The results showed that the topology and its control method are efficient in obtaining a high-quality output with an improved total harmonic distortion (THD).